Strategi Pemasaran Digital untuk Meningkatkan Daya Saing Koperasi Merah Putih di Era Ekonomi Digital - Evi Sintia; Hendra Riofita (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
The purpose of this study is to examine the digital marketing strategies used by the Merah Putih Cooperative to increase their competitiveness in the digital economy era. Cooperatives are forced to adapt to advances in information technology and changes in consumer behavior. They utilize digital platforms for promotions and communication. This study uses a qualitative approach with a literature study method (library research). Data collected from this study comes from various articles, journals, and academic sources related to cooperative digital marketing. Data analysis techniques were conducted descriptively by identifying, grouping, and summarizing the results of previous research. The results show that digital marketing is crucial for increasing market reach, increasing cooperative visibility, enhancing branding, and building consumer trust and loyalty. It is proven that more effective and targeted promotions can be carried out better by using social media, marketplaces, websites, and consumer data analysis. Furthermore, digital marketing strategies help businesses understand customer needs and build more interactive relationships with them. However, digital marketing still faces many challenges, including low digital literacy levels, limited human resources, and a lack of technological infrastructure support. Consequently, for cooperatives to optimize digital technology and survive in contemporary economic competition, ongoing training, mentoring, and policy support are required.